QUANTITATIVE ANALYSIS OF ASBESTOS FIBRES IN OPHIOLITIC ROCKS USED AS AGGREGATES AND HAZARD RISK ASSESSMENT FOR HUMAN HEALTH - Rigopoulos, I.; Tsikoura, B.; Pomonis, P.; Karipi, S.; Hatzipanagiotou, K. (Bulletin of the Geological Society of Greece, 2010)
This study focuses on the quantification of asbestiform minerals in basic and ultrabasic rocks from ophiolite suites of central and northern Greece. A combination of different methods were used for the detailed investigation of the samples, conducted in the following stages: (i) petrographic examination of thin sections with a polarizing microscope, (ii) mineral phase analysis using X-ray diffraction, (iii) determination of the fibrous mineral composition on polished thin sections using scanning electron microscopy, (iv) image analysis of back scattered electron images and secondary electron images, to quantify the dangerous asbestiform crystals. SEM is proved to be the most powerful tool for the detailed investigation of fibrous minerals, although polarized microscopy and XRD are necessary tools for a preliminary identification of these minerals. Basic rocks contain various amounts of actinolite, however not all crystals comprise asbestiform fibres. A conspicuous feature observed during careful petrographic analysis is that many of the non as best form actinolite crystals are broken up along their cleavage planes. Rocks with such features need specific consideration since these crystals may subsequently release numerous fibrous cleavage fragments during the production processes and in-service deterioration of aggregates. Among the serpentinized ultrabasic samples, only one contains chrysotile, while the other samples contain antigorite and lizardite.